Thrombin Based Photothermal‐Responsive Nanoplatform for Tumor‐Specific Embolization Therapy. Issue 52 (2nd November 2021) - Yin, Jiajia; Wang, Xiaorui; Sun, Xu; Dai, Hanming; Song, Xuejiao; Li, Buhong; Zhang, Yewei; Chen, Peng; Dong, Xiaochen
Abstract: The specific coagulation in the tumor vasculature has the potential for the ablation of solid tumors by cutting off the blood supply. However, the safe delivery of effective vessel occluding agents in the tumor‐specific embolization therapy remains challenging. Herein, it is reported that the photothermal responsive tumor‐specific embolization therapy based on thrombin (Thr) is delivered by intravenous injection via the phase‐change materials (PCM)‐based nanoparticles. The wax sealing profile of PCM enables safe delivery and prevents the preleakage of Thr in the blood circulation. While in the tumor site, the thermal effect induced by IR780 triggers the melting of PCM and rapidly releases Thr to generate coagulation in the tumor blood vessels. Based on the safe delivery and controllable release of Thr, thermal responsive tumor‐specific embolization therapy could be achieved with high efficiency and no significant damage to normal organs and tissues. The safe administration of Thr to induce vascular infarction in tumors based on PCM nanoparticles in this work shows a promising strategy for improving the therapeutic specificity and efficacy of coagulation‐based tumor therapy. Abstract : A nano‐carrier based on phase‐change materials is constructed to achieve the safe intravenous injection and controllable release of thrombin through a simple method. The smart nano‐carrier‐induced tumor‐vascular infarction improved the therapeutic specificity and efficacy of coagulation‐based tumor therapy.